Music with a Message: Words, Music and Propaganda 2 (University of Maribor Press, 2025)
Music with a Message: Words, Music and Propaganda 2 explores ways in which music in connection with various disciplines represents a voice of political critique, cultural expression and resistance. The chapters, written by established academics as well as graduate students, bring a plethora of fresh views from multiple fields like literature, language, English language teaching, as well as cultural, social and political studies. Musical genres addressed are as diverse as the approaches to propaganda; they expand from various ethnic folk and pop music, rap, alternative rock and metal to national anthems, cartoon soundtracks and musicals. This collection appeals to scholars, and students as well as enthusiasts interested in the profound cultural and ideological impact of music.